2016
DOI: 10.1142/s0217984916501724
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of defect subsystem in zinc telluride crystals

Abstract: Using method on the base of minimizing of thermodynamic potential in "crystal-vapor" system as a function of defect concentration the equilibrium concentration of point defects and free charge carriers in zinc telluride (ZnTe) crystals have been calculated depending on the technological factors of two-temperature annealing (annealing temperature T and vapor pressure P Zn of zinc or P Te of tellurium). It is shown that the dominant defects are zinc vacancies the charge state of which depends on the technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It should be noted that LaMnO3 with a perovskite structure can have both cubic (Pm -3m) and rhombic (Pnma) lattices. Calculations have been carried out similarly to the methods described in [38][39][40][41] showed that LaMnO3 with a perovskite structure forms exactly a cubic crystal lattice. Figure 1b shows a model of the crystal structure of the obtained material of LaMnO3 (view along the C axis), which shows that the Mn cation is in an octahedral environment of O 2anions.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that LaMnO3 with a perovskite structure can have both cubic (Pm -3m) and rhombic (Pnma) lattices. Calculations have been carried out similarly to the methods described in [38][39][40][41] showed that LaMnO3 with a perovskite structure forms exactly a cubic crystal lattice. Figure 1b shows a model of the crystal structure of the obtained material of LaMnO3 (view along the C axis), which shows that the Mn cation is in an octahedral environment of O 2anions.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds, in which structure cations of heavy atoms are located within the anionic sublattice of light atoms, can reveal interesting physical properties [22,23].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Quantum chemical (QC) calculations were performed using the Firefly QC program package [44], which is based on the GAMESS (US) source code [45]. The calculations were performed based on the hybrid functional B3LYP that used the Becke GGA functional for the exchange energy, and the Lee-Yang-Parr GGA functional for the correlation energy [46,47]. For the calculations, we employed lattice parameters, symmetry information, and atomic coordinates obtained during the crystal structure refinement of the Cu2CoHf3S8 and using literature data for CuCo2S4 and CuHf2S4 compounds.…”
Section: Methodsmentioning
confidence: 99%